2015
DOI: 10.4067/s0718-58392015000400014
|View full text |Cite
|
Sign up to set email alerts
|

Reference evapotranspiration estimates based on minimum meteorological variable requirements of historical weather data

Abstract: Reference evapotranspiration (ET 0 ) is critical for agricultural and urban planning, irrigation scheduling, regional water balance studies, and agroclimatological zoning. The objective of this study was to estimate ET 0 based on methods with minimum meteorological variable requirements and on empirical models to predict solar radiation. These alternative methods were compared to the FAO Penman-Monteith method by using more than 80 yr of historical weather data. Alternative methods were adapted from the standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It can be shown that the model constructed in this study can better estimate the watermelon ET under the conditions of sub-membrane drip irrigation in the Hexi Oasis by using LAI and meteorological factors. ET 0 is a critical parameter for calculating crop water requirements and irrigation management (Ahmad et al, 2017;Kadam et al, 2021), and the ET 0 calculated based on the P-M equation is directly affected by the local climate (Neto et al, 2015;Borges and Pinheiro, 2019). In this study, the average ET 0 values during the watermelon growing season were found to be 4.15 mm (2020) and 4.33 mm (2021), with the relatively smallest ET 0 at MS.…”
Section: Et Estimation Model and Error Analysismentioning
confidence: 67%
“…It can be shown that the model constructed in this study can better estimate the watermelon ET under the conditions of sub-membrane drip irrigation in the Hexi Oasis by using LAI and meteorological factors. ET 0 is a critical parameter for calculating crop water requirements and irrigation management (Ahmad et al, 2017;Kadam et al, 2021), and the ET 0 calculated based on the P-M equation is directly affected by the local climate (Neto et al, 2015;Borges and Pinheiro, 2019). In this study, the average ET 0 values during the watermelon growing season were found to be 4.15 mm (2020) and 4.33 mm (2021), with the relatively smallest ET 0 at MS.…”
Section: Et Estimation Model and Error Analysismentioning
confidence: 67%
“…As in the HS method, radiation is also required at the "top" of the atmosphere, whose variation is defined based on the day of the year and latitude. In the conception of method, it was taken as the basis Borges Junior model for calculation of solar radiation, proposed in Steidle Neto et al (2015), adapting to obtain the ET 0 , having the following general equation:…”
Section: Estimation Of Reference Evapotranspiration Etmentioning
confidence: 99%
“…With great importance for agricultural and urban planning, irrigation managing, regional water balance studies, and agroclimatic zoning (Steidle Neto et al, 2015), evapotranspiration is one of the variables affected by the atmospheric aerosol presence due to changes in the global solar radiation on earth surface. Some observational studies have been attempted to evaluate the aerosol direct effects on the latent heat flux at site levels (Murthy et al, 2014;Steiner et al, 2013;Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%